(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study investigates the impact of logistics service efficiency in delivery applications on Saudi consumer satisfaction and marketing growth. Conducted as a field study in Jeddah with a sample of (41) delivery app users, the research highlights the increasing reliance on digital logistics services in the Saudi market and the evolving expectations of consumers in a rapidly transforming digital environment. Adopting a descriptive-analytical approach, data were collected through a structured questionnaire and analyzed using SPSS techniques, including regression analysis, internal consistency, and principal component analysis (PCA). Results indicate a significant relationship between logistics efficiency and consumer satisfaction, with logistics efficiency also explaining a considerable share of marketing growth. The most influential dimensions identified were responsiveness, transparency, accuracy of information, and ease of use. The study contributes theoretically by linking digital transformation, logistics efficiency, and consumer behavior, while offering practical insights for delivery service providers aiming to enhance customer loyalty and achieve sustainable market expansion.